2020
DOI: 10.1093/mnras/staa155
|View full text |Cite
|
Sign up to set email alerts
|

VVV-WIT-01: highly obscured classical nova or protostellar collision?

Abstract: A search of the first Data Release of the VISTA Variables in the Via Lactea (VVV) Survey discovered the exceptionally red transient VVV-WIT-01 (H − K s = 5.2). It peaked before March 2010, then faded by ∼9.5 mag over the following two years. The 1.6-22 µm spectral energy distribution in March 2010 was well fit by a highly obscured black body with T ∼ 1000 K and A K s ∼ 6.6 mag. The source is projected against the Infrared Dark Cloud (IRDC) SDC G331.062−0.294. The chance projection probability is small for any … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…This was a somewhat serendipitous discovery, using data from the WISE satellite (Wright et al 2010) (with pre-outburst data from Spitzer/ GLIMPSE Benjamin et al 2003). It followed from our investigation of the (unrelated) infrared transient VVV-WIT-01 (Lucas et al 2020), though 22 additional high amplitude mid-infrared variables were found in the same search (see section 2.1).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…This was a somewhat serendipitous discovery, using data from the WISE satellite (Wright et al 2010) (with pre-outburst data from Spitzer/ GLIMPSE Benjamin et al 2003). It followed from our investigation of the (unrelated) infrared transient VVV-WIT-01 (Lucas et al 2020), though 22 additional high amplitude mid-infrared variables were found in the same search (see section 2.1).…”
mentioning
confidence: 83%
“…The search was undertaken during an investigation of a very red transient, VVV-WIT-01, which was projected against an IRDC from the list of Peretto & Fuller (2009), see Lucas et al (2020). The covering fraction of IRDCs in the GLIMPSE region is only 1-2% (depending on whether unconfirmed IRDCs are included) so it was thought that VVV-WIT-01 might be a pre-main sequence event.…”
Section: Methodsmentioning
confidence: 99%
“…Radio detections could also overcome extinction effects and gaps in optical novae monitoring, which account for a large discrepancy of ∼30-50 novae between observed and theoretical discovery rates per year (Shafter 2017;De et al 2021). For example, VVV-WIT-01 was classified as a classical nova using only radio and IR multiwavelength analysis, with no detection in optical (Lucas et al 2020). The availability of a statistically robust sample of novae observed in radio would also aid in more accurate ejecta mass predictions.…”
Section: Detectability Of Classical Novae With Askapmentioning
confidence: 99%
“…A few previously unclassified variable sources that we call "WIT" objects-short for What Is This?-have been discovered by the VISTA Variables in the Vía Láctea (VVV) survey (Minniti et al 2010). These represent a wide variety of extreme or rare astrophysical phenomena, including a very reddened novae or supernova or a protostellar collision (VVV-WIT-01; Lucas et al 2020), an extragalactic radio source violently variable in the near-IR (VVV-WIT-04; Saito et al 2019b), another Tabby star or Mamajek object (VVV-WIT-07; Saito et al 2019a) and a giant star that blinked (VVV-WIT-08 Smith et al 2021).…”
Section: Introductionmentioning
confidence: 99%